(untitled) (Revista Contexto & Saúde, 2025)
Lower-limb amputations result in significant impairments in functional capacity, balance, and motor coordination. Among these functional limitations, the elevated incidence of falls in this population is particularly prominent, with such outcomes being directly associated with age. Accordingly, the objective of this study was to investigate the influence of age on functional performance and fall risk in individuals with transfemoral amputation. This is an observational, analytical, cross-sectional study, comprising a sample of 18 male individuals with transfemoral amputation, aged between 30 and 80 years. The following instruments were employed for the assessments: Amputee Mobility Predictor (AMP), Functional Independence Measure (FIM) and the Timed Up and Go (TUG) test. Descriptive statistics and the Spearman correlation test were applied (p<0.05). A moderate, inverse, and significant correlation was observed between age and the Amputee Mobility Predictor (AMP), as well as the total and motor domains of the Functional Independence Measure (FIM) (p=0.01, p=0.05, and p=0.01, respectively). In addition, age demonstrated a strong and significant correlation with the Timed Up and Go (TUG) test (p<0.000), indicating a greater risk of falls. Age had a negative impact on both functionality and fall risk, as higher age was associated with longer completion time in the TUG test and poorer functional performance assessed by the AMP and FIM. These findings may contribute to the rehabilitation process by promoting greater independence and quality of life in individuals with lower-limb amputation.